1999
DOI: 10.1063/1.477956
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical aspects of mixing schemes in ethanol–water mixtures in terms of the excess partial molar activation free energy, enthalpy, and entropy of the dielectric relaxation process

Abstract: Dielectric relaxation measurements on the ethanol–water mixture for the entire concentration range in very small increments were carried out using TDR in the frequency range from 300 MHz to 25 GHz at 20 °C, 22.5 °C, and 25 °C. The activation enthalpy ΔH and entropy ΔS for the mixtures were separated from the activation free energy ΔG, and hence the excess partial molar activation free energy, enthalpy, and entropy for ethanol, ΔGEAE, ΔHEAE, and ΔSEAE, and those for water, ΔGWE, ΔHWE, and ΔSWE were calculated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 38 publications
10
120
1
Order By: Relevance
“…The increase in the relaxation time upon cooling reflects the slowingdown process of the rearranging cooperative motion. The addition of the water to the ethanol slightly reduces the acoustic relaxation times, consistent with the change in the dielectric relaxation times [15]. Considering the consistent temperature dependence of both relaxation times shown in Fig.6, the origin of the acoustic relaxation process and the dielectric relaxation process probed by the two experimental methods seems to be the same.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The increase in the relaxation time upon cooling reflects the slowingdown process of the rearranging cooperative motion. The addition of the water to the ethanol slightly reduces the acoustic relaxation times, consistent with the change in the dielectric relaxation times [15]. Considering the consistent temperature dependence of both relaxation times shown in Fig.6, the origin of the acoustic relaxation process and the dielectric relaxation process probed by the two experimental methods seems to be the same.…”
Section: Discussionsupporting
confidence: 59%
“…For comparison, the dielectric relaxations of pure ethanol and ethanolwater mixture (20%) from Ref. [15], measured by the time domain reflectometry, are also shown. The increase in the relaxation time upon cooling reflects the slowingdown process of the rearranging cooperative motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] Dielectric relaxation and nuclear magnetic resonance spectroscopies support the clustering explanation while also revealing reduced liquid mobility. [36][37][38][39][40][41] Using Raman spectroscopy, Ben-Amotz et al have concluded that the observed clustering in alcohol-water mixtures is a result of random, rather than hydrophobic, interactions. 42,43 In contrast, some femtosecond midinfrared spectroscopy experiments have shown that water surrounding the aliphatic groups of the alcohols displays significantly slowed dynamics relative to the bulk, lending support to the model in which the measured negative excess entropy is attributed to water forming clathrate-like structure around the hydrophobic groups of the alcohols.…”
Section: -17mentioning
confidence: 99%
“…Even though molecules like methanol and water can be mixed over the whole concentration range, the methyl groups still tend to cluster to some degree in methanol solutions 26 . Dielectric relaxation measurements of a number of alcohol/water mixtures have revealed mixing to be a complex function of alcohol concentration [27][28][29][30] . Molecular simulation of such mixtures reproduces most features of these mixtures at least qualitatively 31,32 .…”
Section: Introductionmentioning
confidence: 99%